Popular TV Fiction: Cultural Identities, Unconscious Malay Psyche, and Youth - Idrus, Mohd Muzhafar; Hashim, RS; Mydin, RM; Saad, NSM; Puteh-Behak, F; Darmi, R (American Scientific Publishers, 2024)
This paper discusses how Malay female youth relate to popular TV fiction Julia, On Dhia, and Adam and Hawa through audience responses. Specifically, it examines how TV fiction allow Malay female viewers to negotiate against complex Malay cultural fabrics. One of the most important findings is that voices by female youth describe intricacies of donning the robe of modern, Malay youth. On one level, these voices surmise and react to cultural and religious taboo. On another level, however, they identify the TV fiction with familiar, localized markers. This paper implies that in their engagement with Western-imposed globalization issues demonstrated in TV fiction, they allow Malay female youth to return to their familiar, cultural, local Malay spaces. It further proposes to understand this engagement with globalization and return to local, cultural routes as unconscious Malay psyche through which these female voices (re)imagine cultural identities, in some cases, by not simply substituting or integrating global and local values. By telling their stories, how some Malay subjects participate in and become involved with social sphere, eventually gesturing to religious, cultural labels are shown.